Justice Beyond Legislation: The Evolution of Judicial Activism - Gupta, Shivangi (Trinity Law Review, 2026)
The Indian judiciary has played a significant role in shaping the country's constitutional framework by ensuring that justice is not confined to the literal interpretation of statutory provisions. Over the years, judicial activism has evolved as a constitutional response to situations where legislative action has been delayed, executive authorities have failed to fulfil their obligations, or the protection of fundamental rights has required immediate judicial intervention. This development has enabled the courts to address complex social, economic, and environmental issues while reinforcing the principles of constitutional governance.This paper examines the growth of judicial activism in India and analyses the factors that have contributed to its emergence as an important feature of constitutional adjudication. It explores the constitutional provisions that empower the higher judiciary to protect individual rights and uphold the basic values of the Constitution. Attention is given to the development of Public Interest Litigation, which has widened access to justice by allowing courts to hear matters affecting disadvantaged and vulnerable sections of society. The paper also discusses how judicial decisions have influenced areas such as environmental protection, gender justice, administrative accountability, and the expansion of fundamental rights.While acknowledging the positive contribution of judicial activism, the study also considers the concerns associated with increasing judicial intervention in matters traditionally falling within the domain of the legislature and the executive. It examines the continuing debate on judicial overreach and the need to preserve the constitutional principle of separation of powers. The paper argues that an independent judiciary must remain vigilant in protecting constitutional rights, but such intervention should be guided by constitutional discipline and institutional restraint.The research adopts a doctrinal method based on the analysis of constitutional provisions, judicial decisions, and academic literature. It concludes that judicial activism has strengthened constitutional democracy by promoting accountability and protecting individual liberties. At the same time, its long-term legitimacy depends upon maintaining an appropriate balance between judicial innovation and respect for the constitutional responsibilities of the other organs of the State.
Keywords: United Nations; Humanitarian Intervention; Afghanistan; UN and Health